Da institucionalização e efetividade da mediação à luz do código de processo civil e da lei nº 13.140/15 quanto à administração pública - Santos, Cláudia Lúcia Soares da Silva (2019)
This dissertation analyzes the applicability, effectiveness and limitations of mediation in the litigation involving Public Administration. It emphasizes the paradigm of consensualism in relation to its conflicting relations. Thus, with the advent of Law 13.140 / 15, being one of the mechanisms of self-composition used in extra-judicial and judicial scope, the Measurement is studied in a search for a possible non-adversarial method of conflict resolution. In the first chapter, the paper positions the current scenario of Mediation and Consensualism in the public sphere in resolving disputes in Brazil, from the development of consensualism to changes in the paradigms of Administration. In the second, it is the re-reading of some precepts of Administrative Law that may constitute an obstacle to the admission of the consensual means of institutional and procedural applicability of Mediation of conflicts, involving Public Administration, as its delimitation, and also, the scope of its scope and procedure, as well as situate the subject in the context of mediation in the conflicts that encompass it in the consensual administrative action. The third chapter presents the effectiveness of mediation in the Public Administration with important paradigms to understand the issue of: the composition of conflicts in the Public Administration and also the necessary adaptation of the jurisdictional function to new forms of conflict resolution beyond the contribution of mediation in Law For the adjudication. Finally, it discusses consensual experiences lived in the Attorney General's Office of the City of São Paulo with the purpose of revealing experiences and practical obstacles to the adoption of consensual means.